Controlling Interfacial Charge Transfer and Fill Factors in CuO-based Tandem Dye-Sensitized Solar Cells - Langmar, Oliver; Fazio, Ettore; Schol, Peter; De La Torre, Gema; Costa, Ruben Dario; Torres, Tomas; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2019)
We designed and synthesized a series of novel electron-accepting zinc(II)phthalocyanines (ZnPc) and probed them in p-type dye sensitized solar cells (p-DSSCs) by using CuO as photocathodes. By realizing the right balance between interfacial charge separation and charge recombination, optimized fill factors (FFs) of 0.43 were obtained. With a control over fill factors in p-DSSCs in hand we turned our attemtion to i-DSSCs, in which we combined for the first time CuO-based p-DSSCs with TiO2 -based n-DSSCs using ZnPc and N719. In the resulting t-DSSCs, the V-OC of 0.86 V is the sum of those found in p- and n-DSSCs, while the FF remains around 0.63. It is only the smaller J(SC)s in t-DSSCs that limits the efficiency to 0.69%.
CRIS-Team WoS Importer:2019-04-12

Fused Hexabenzocoronene-Porphyrin Conjugates with Tailorable Excited-State Lifetimes - Oleszak, Christoph; Schol, Peter; Ritterhoff, Christian; Krug, Marcel; Martin, Max; Bo, Yifan; Meyer, Bernd; Clark, Timothy; Guldi, Dirk Michael; Jux, Norbert (Angewandte Chemie International Edition, 2024)
A new clear-cut strategy for fusing N-heterocyclic and carbon-pure systems is introduced en route to a versatile platform of multi-purpose tetrapyrrolic chromophores. In particular, three novel C−C bond-fused porphyrin-hexabenzocoronene (HBC) conjugates were synthesized under oxidative cyclodehydrogenation conditions, starting from tailor-made nickel porphyrin precursors. The fusion of the individual aromatic systems via 5-membered rings led to highly soluble π-extended porphyrins in excellent yields. The resulting porphyrin-HBC conjugates exhibit absorption cross-sections that are of interdisciplinary interest in the ever-growing field of organic photovoltaics and near-infrared (NIR) dyes. Quantum chemical calculations show that the newly formed 5-membered rings induce biradicaloid character in the porphyrin core, which has a strong impact on excited state lifetimes. This is confirmed by a thorough optoelectronic and time-resolved characterization in order to understand these unique features better. Broadened absorption characteristics go hand-in-hand with short-lived excited states with up to six orders of magnitude faster decay rates.
CRIS-Team Scopus Importer:2024-10-25
Keywords: biradicaloids; porphyrinoids; post-functionalization; Scholl oxidation; π-extension

Harnessing multiple generated excitons from intermolecular singlet fission of perylene–monoimides in a p-type dye-sensitized solar cell - Papadopoulos, Ilias; Schol, Peter; Garcés-Garcés, Jose; Sastre-Santos, Ángela; Fernández-Lázaro, Fernando; Guldi, Dirk Michael (Solar Energy, 2023)
A perylene-monoimide (PMI) monomer is functionalized with a benzoic acid to support immobilization on copper oxide (CuO) / nickel oxide (NiO) p-type semiconductors in order to construct p-type dye-sensitized solar cells (DSSCs). All devices are fully characterized by means of J-V, electrochemical impedance, and incident photon-to-current conversion efficiency (IPCE) measurements. Their optimization in terms of PMI uptake, iodine / Li+ addition and layer thickness lead to efficiencies as high as 0.07 %. For PMIs, the favorable relationship between their respective singlet and triplet excited state energies of 2.36 and 1.12 eV enable thermodynamically driven singlet fission (SF). The strong inter–PMI interactions on the semiconductor surface allow for an efficient and fast intermolecular SF. The formed correlated triplet pair ((T1)(T1)) is corroborated by means of time-resolved transient absorption spectroscopy (TAS) and partakes in an interfacially charge injection into the CuO / NiO semiconductors within the p-type DSSCs.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Intermolecular singlet fission; P-type dye sensitized solar cells; Perylene-monoimides; Time-resolved spectroscopy

Improving charge injection and charge transport in CuO-based p-type DSSCs-a quick and simple precipitation method for small CuO nanoparticles - Langmar, Oliver; Ganivet, Carolina R.; Schol, Peter; Scharl, Tobias; De La Torre, Gema; Torres, Tomas; Costa Riquelme, Rubén Dario; Guldi, Dirk Michael (Journal of Materials Chemistry C, 2018)
Herein, we introduce a co-precipitation synthesis of CuO, which produces small and uniform nanoparticles (∼12 nm) with a specific surface area of 97.3 m2 g-1. The resulting CuO nanoparticles are superior to the commercial ones, which have previously been used to prepare p-type DSSCs. In turn, we compared p-type DSSCs consisting of CuO-based photocathodes based on newly synthesized and commercial nanoparticles. Devices based on new CuO nanoparticles enable higher dye loadings, and, in turn, superior short-circuit current densities and efficiencies. To corroborate our findings, electrochemical impedance spectroscopy and intensity modulated photocurrent spectroscopy assays were conducted, revealing a better charge injection and faster charge transport for those photocathodes featuring the new CuO nanoparticles.
CRIS-Team Scopus Importer:2022-04-14

Intrinsic and Extrinsic Incorporation of Indium and Single-Walled Carbon Nanotubes for Improved ZnO-Based DSSCs - Schol, Peter; Zhang, Wen Shan; Scharl, Tobias; Kunzmann, Andreas; Peukert, Wolfgang; Schröder, Rasmus R.; Guldi, Dirk Michael (Advanced Energy Materials, 2022)
A common goal in renewable energy research is the production of semiconductor layers with matching additives to gain desirable effects and advantages. Important examples are adjustment of the band gap, enhancing the conductivity, tailoring roughness of the semiconductor, or reducing the recombination rate of charge carriers. In this work a twofold approach is demonstrated. First, the intrinsic incorporation of indium into zinc oxide tunes the band gap of the semiconductor layer of the DSSCs. Second, single-walled carbon nanotubes (SWCNT) as an extrinsic additive improves the charge transport capabilities. To better combine the SWCNTs with the semiconductor layer a protective ZnO shell is grown on the SWCNTs. A combination of current–voltage, incident photon to current efficiency, and electrochemical impedance spectroscopic assays corroborates the positive effects of both additives on the cell performance. The effective charge-carrier diffusion lengths are enhanced from 0.52 µm for pure ZnO to 5.12 µm for low SWCNT concentrations and 15 mol% of indium. This, as well as the increase in collection efficiency from 30.3% to 62.3% enables enhanced transport in these novel devices. A final device utilizing 0.1 wt% SWCNT@ZnO20nm and In15Zn85O yields a current density of 16.49 mA cm−2 and an efficiency of 4.46%.
CRIS-Team Scopus Importer:2022-03-11
Keywords: indium–zinc oxide photoanodes; n-type DSSCs; semiconductor doping; single-wall carbon nanotubes

Non-Covalent Postfunctionalization of Dye Layers on TiO2 - A Tool for Enhancing Injection in Dye-Sensitized Solar Cells - Luchs, Tobias; Zieleniewska, Anna; Kunzmann, Andreas; Schol, Peter; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2021)
We report on newly tailored dye layers, which were employed, on one hand, for covalent deposition and, on the other hand, for non-covalently post-functionalizing TiO2 nanoparticle films. Our functionalization concept enabled intermixing a stable covalent attachment of a first layer with a highly versatile and reversible hydrogen bonding through the Hamilton receptor-cyanuric acid binding motif as a second layer. Following this concept, we integrated step-by-step a first porphyrin layer and a second porphyrin/BODIPY layer. The individual building blocks and their corresponding combinations were probed with regard to their photophysical properties, and the most promising combinations were implemented in dye-sensitized solar cells (DSSCs). Relative to the first porphyrin layer adding the second porphyrin/BODIPY layers increased the overall DSSC efficiency by up to 43 %.
CRIS-Team WoS Importer:2021-03-12

Photon- and Charge-Management in Advanced Energy Materials: Combining 0D, 1D, and 2D Nanocarbons as well as Bulk Semiconductors with Organic Chromophores - Cadranel, Alejandro; Haines, Philipp; Kaur, Ramandeep; Menon, Arjun; Münich, Peter Wilhelm; Schol, Peter; Guldi, Dirk Michael (Advanced Energy Materials, 2020)
In this contribution, seminal works in the area of photon- and charge-management are highlighted with focus on covalent electron donor-acceptor conjugates built around porphyrins (Ps), on one hand, and 0D, 1D, and 2D nanocarbons, on the other hand. Photons in these conjugates are managed by Ps, while 0D, 1D, and 2D nanocarbons serve as the active component, which enable managing charges. With a few leading examples, it can be explored much beyond the simple photon- and charge-management characterization and emphasize photovoltaics and photocatalysis to convert and store energy. This contribution concludes by highlighting recent progress in mixing and matching the unique charge-management features of nanocarbons in the design of multidimensional nanocarbons.
CRIS-Team Scopus Importer:2020-12-11
Keywords: charge management; nanocarbons; photon management; solar-energy conversion

Understanding the Visible Absorption of Electron Accepting and Donating CNDs - Reva, Yana; Jana, Bikash; Langford, Daniel; Kinzelmann, Marina; Bo, Yifan; Schol, Peter; Scharl, Tobias; Zhao, Xinyi; Crisp, Ryan; Drewello, Thomas; Clark, Timothy; Cadranel, Alejandro; et al. (Small, 2023)
Carbon nanodots (CNDs) synthesized from citric acid and formyl derivatives, that is, formamide, urea, or N-methylformamide, stand out through their broad-range visible-light absorbance and extraordinary photostability. Despite their potential, their use has thus far been limited to imaging research. This work has now investigated the link between CNDs’ photochemical properties and their chemical structure. Electron-rich, yellow carbon nanodots (yCNDs) are obtained with in situ addition of NaOH during the synthesis, whereas otherwise electron-poor, red carbon nanodots (rCNDs) are obtained. These properties originate from the reduced and oxidized dimer of citrazinic acid within the matrix of yCNDs and rCNDs, respectively. Remarkably, yCNDs deposited on TiO2 give a 30% higher photocurrent density of 0.7 mA cm−2 at +0.3 V versus Ag/AgCl under Xe-lamp irradiation (450 nm long-pass filter, 100 mW cm−2) than rCNDs. The difference in overall photoelectric performance is due to fundamentally different charge-transfer mechanisms. These depend on either the electron-accepting or the electron-donating nature of the CNDs, as is evident from photoelectrochemical tests with TiO2 and NiO and time-resolved spectroscopic measurements.
Created from Fastlane, Scopus look-up
Keywords: carbon nanodots; excited state; photoelectrochemistry; semiconductors; time-resolved spectroscopy